Polimery ksylilenowe - niezwykłe tworzywa wielkocząsteczkowe - Gazicki-Lipman, Maciej (Wydawnictwo Politechnika Łódzka, 2007)
Having been discovered in the forties and developed in the sixties of the twentieth century, poly(xylylenes) owe their current technological interest to the progress made in microtechnology. Mainly known under the trade name of Parylene, xylylene polymers constitute a separate class of polymeric materials. This is due to the fact that they are produced in the form of thin surface coatings, resulting from a chemical vapor deposition process and from its vacuum polymerization/deposition variant in particular. There are several well established industrial applications of poly(xylylenes ), among which protection of electronic circuitry (printed board circuits, hybrid circuits, etc.) against the environmental effects is stili the major one. Apart from that, xylylene polymers are being applied as coatings for ferrite cores, rear earth magnets, elastomer products and, first of all, for various biomedical appliances. Currently developed applications in microtechnology comprise various microfluidic microelectromechanical systems (microscopic pumps, valves, flow meters, chromatographic columns, etc.) as well as organie semiconductor devices, such as organie field effect transistors, organie light emitting diodes, and even entire active matrix displays. The book offers a comprehensive, monographic description of xylylene polymers. lt begins with a review of historical developments, leading to the discovery of xylylene and its polymer. lt then describes the Union Carbide process of Parylene manufacture. Succesive chapters are devoted to the mechanism of poly(p-xylylene) synthesis, to the structure of xylylene polymers and to the spectroscopy of these materials. Finally, the last two chapters deal with their utility properties and with their applications. Particular attention is given to the most modern applications of poly(p-xylylenes), namely those in the area of microtechnology.
Red. serii : Wodziński, Piotr
Keywords: polimery ksylilenowe; polimery; polimeryzacja; spektroskopia; ksyleny - pochodne; xylylene polymers; polymers; polymerization; spectroscopy; xylenes - derivatives